Digital Service of Practice licensing for Medical Personnel and Health Facilities with Dashboard System - Domi Sepri; Ahmad Fauzi; Suci Eka Putri (Journal of Information System Research (JOSH), 2023)
Health workers in the rules must have a requirement in the form of a Practice License in carrying out medical and health activities at a medical practice site. Likewise, health facilities that want to open medical practices must be recorded and have a license to practice issued by the local district / city Health Office. The license to practice medical personnel and health facilities so far in the city of Bukittinggi in the service process is still done manually, making it ineffective for data management and difficult to obtain information. Therefore, a technological innovation is needed for the process of digitizing the service of issuing a web-based license to assist the process of licensing services for licenses to practice medical personnel and health facilities that are fast and effective in producing such correspondence needs. This web-based application was developed using the waterfall model because the stages of the process are passed step by step to get good results. This application on the main page is also displayed with the concept of a dashboard system, making it easier for users to view general data in the application such as data on medical personnel and health facilities that will expire their medical licenses. This application has been tested and used for services to the government and helps in the process of correspondence and evaluating the control process on the licensing of health workers.